A study on assessment of knowledge, attitude and practice of premenstrual syndrome among female in urban area - Sireesha, V.; Fatima, Faiqua; Sultana, Shafeen; Kumar, M. Shiva Sai; ., Sumaya; Tadikonda, Rama Rao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Premenstrual syndrome (PMS) is a significant clinical disorder affecting a substantial percentage of women. This study aims to investigate the existence, knowledge, and attitude of female students towards PMS. Methods: A cross-sectional descriptive study was conducted, with 250 female participants between the ages of 18 to 30 years. The participants completed a self-reporting menstrual distress questionnaire (MDQ) and a standardized health questionnaire to assess the prevalence and severity of premenstrual symptoms and also to assess the knowledge, attitude, and practice of PMS for subjective perceptions of health, stress, lifestyle, and demographic variables. The questionnaire was set in four parts, one each to assess the knowledge, the attitude, and practices regarding PMS and one to assess the gap between self-perceived PMS and actual PMS. The data were analysed using descriptive statistics. Results: The results revealed that 80% of the participants reported experiencing PMS, but only 48% met the criteria defined by the American College of Obstetricians and Gynecologists (ACOG). The most common symptoms reported were irritability, mood swings, headache, fatigue, and menstrual cramps. PMS had a significant impact on participants’ normal life, with 60.4% reporting disturbances in their routine. While 51.2% believed that PMS/menstrual leave should be an option at universities, only 39.2% supported the idea at the workplace. Conclusions: Surprisingly, over 60% of participants did nothing to relieve their PMS symptoms. So, there is a significant impact of PMS in the lives of urban women and it is also a common problem all over the globe. The study underscores the need for increased awareness and education about PMS and its management, as well as the importance of promoting a stress-free environment to mitigate its impact on women’s quality of life.